Akumulasi Timbal (Pb) Dan Tembaga (Cu) Pada Ikan Kuniran (Upeneus Sulphureus) Di Perairan Estuaria Teluk Palu - Dessy Amalia Lubis; Irwan Said; Suherman Suherman (Jurnal Akademika Kimia, 2014)
Estuarine waters is the meeting place of various estuaries to the open sea, which causes the estuarine water vulnerable to pollution by heavy metals. The source of pollution in the waters may come from gold mining activities, workshop waste, agricultural waste, motor vehicles activities, and domestic industrial activity. The pollutant materials may vary and one of which is heavy metal such as Pb dan Cu. Estuarine water of Palu Bay extends along a semicircle around the city. The bay is also the source of income of the lical fishermen. One of the commodity fish in the water is yellow goat fish (Upeneus sulphureus).This study aimed to determine the levels of lead (Pb) and copper (Cu) containing in yellow goat fish (upeneus sulphureus) that live in the water of the Palu gulf, Central Sulawesi Tengah. This study started by making field notes on the observation around Palu Bay. The next stage is to do the yellow goat fish sampling (Upeneus sulphureus) in the Palu Gulf then continuing to conduct the research in the chemistry Laboratory in Teacher Training and Education Factulty. To measure the level of lead and copper metal in yellow goat fish (Upeneus sulphureus) in Palu Bay, the researcherof, employed Direct Spectro tool. The data obtained were analyzed descriptively, which compared to the standard quality of food by the General Director of Drug and Food Control No. 03725/B/SK/VII/89 and ISO 7387:2009. The results showed that levels of lead metal in yellow goat fish (upeneus sulphureus) were 0,567 mg/kg, meaning that the levels of lead metal has exceeded the threshold value of the specified foods (0,3 mg/kg). While the copper metal content in yellow goat fish (Upeneus sulphureus) was 2,237 mg/kg and still below the specified threshold (5 mg/kg).